The Effect of Benefit Sanctions on the Duration of Unemployment - Rafael Lalive; Jan C. van Ours; Josef Zweimüller (Institute for the Study of Labor (IZA), 2002)
This paper investigates the effectiveness of benefit sanctions in reducing unemployment duration. Data from the Swiss labor market allow making a distinction between the effect of a warning that a person is not complying with eligibility requirements and the effect of the actual enforcement of a benefit sanction. We find that both warning and enforcement have a positive effect on the exit rate out of unemployment. Moreover, the stricter the sanction policy the shorter is the duration of unemployment of the non-sanctioned. This can be taken as evidence of a strong ex-ante effect of a strict sanction policy.
Keywords: J64; J68; J65; 330; unemployment duration; benefit sanctions; monitoring; Arbeitslosigkeit; Dauer; Arbeitslosenversicherung; Rechtsdurchsetzung; Schweiz